2012
DOI: 10.1364/oe.20.006808
|View full text |Cite
|
Sign up to set email alerts
|

Light extraction efficiency improvement by multiple laser stealth dicing in InGaN-based blue light-emitting diodes

Abstract: We report a multiple laser stealth dicing (multi-LSD) method to improve the light extraction efficiency (LEE) of InGaN-based light-emitting diodes (LEDs) using a picosecond (Ps) laser. Compared with conventional LEDs scribed by a nanosecond (Ns) laser and single stealth-diced LEDs, the light output power (LOP) of the LEDs using multi-LSD method can be improved by 26.5% and 11.2%, respectively. The enhanced LOP is due to the increased side emission from the large-area roughened sidewalls of the sapphire substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 15 publications
1
34
0
Order By: Relevance
“…The nano-roughened surface allows the photons emitted from the active regions to escape from the LEDs, accordingly, increases the LEE of LED devices. This mechanism for the improvement of light output power in our experiment agrees well with the previously reported [9,11,12]. It is necessary to point out that light output power of sample D is a little lower than sample C. We suspect that the lower output power of sample D is caused by the degradation of crystalline quality in p-GaN layer, which has been showed by XRD FWHMs above.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The nano-roughened surface allows the photons emitted from the active regions to escape from the LEDs, accordingly, increases the LEE of LED devices. This mechanism for the improvement of light output power in our experiment agrees well with the previously reported [9,11,12]. It is necessary to point out that light output power of sample D is a little lower than sample C. We suspect that the lower output power of sample D is caused by the degradation of crystalline quality in p-GaN layer, which has been showed by XRD FWHMs above.…”
Section: Resultssupporting
confidence: 92%
“…This problem seriously hindered the realization of high external quantum efficiency (EQE) of LEDs. Some methods toward improving the LEE of LED devices have been proposed, mainly including photonic crystal (PC) [2,3], localized surface plasmons (LSPs) [4][5][6], patterned substrate [7] and surface roughening [8][9][10][11][12]. Specifically, surface roughening is widely accepted on account of its simple and efficient characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fireflies produce their own light, which needs to be extracted from photocytes found in its bioluminescent organ (called "lantern"). It has been shown in previous works [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] that the firefly Photuris sp. presents a two-dimensional pattern with an asymmetrical triangular profile with sizes in the range of a few micrometers on its lantern cuticle.…”
Section: Introductionmentioning
confidence: 99%
“…[352,353] Bay et al have recently shown that the structure of the cuticle outside of the light-emitting organ increases the efficiency of the light emission by ≈10%. [352] The light-extraction efficiency of synthetic electroluminescent devices, e.g., organic light-emitting diodes (OLEDs), suffers from the same refractive-index-mismatch, [354] and the insight from the firefly lantern structure has been used to improve light-extraction from OLEDs by up to 55%. [353] …”
Section: Bioluminescencementioning
confidence: 99%